A Sketch of the Future of Geography in Ukrainian Realities (Something About the State and Future of Geography) - Chervanyov, I. G. (Ukrainian Geographical Journal, 2025)
The author’s interpretation draws on examples of the involvement of geographical science in significant domestic projects of the past to establish a connection to the present. The latest methodological issues are identified; the author proposes a subject-subject approach as a paradigm for adaptive nature management and the coevolution of the Nature-Human system. The author defines the equivalence (for different purposes) of phenomenology and constructivism. It is proven that geographical knowledge is not objective, unlike in natural science, because it depends on the paradigm, method, criteria, authorship of views, and other factors, which require explicitly indicating and justifying the initial attributes of the study, the available apparatus, and permissible methods of interpreting geodata. In the methodological aspect, the author notes the tendency, caused by the emergence of new technologies, to track changes, analyze them, monitor them, and manage geosystems on a systemic basis. The author considers the overarching task of modern and future geography to be the glaring problem of abandoning the stereotype of science’s retrospective nature in the educational sphere, which is one of the reasons for the image losses of geography and the removal of the specialty “Geography” from the Ministry of Education and Science of Ukraine. He proposes to change the way science is organized and, accordingly, in higher education institutions, from a subject-based (by branches—physical, economic, social, etc.) to a problem-based approach, which is more effective and flexible.
Keywords: geography; phenomenology; constructivism; retrospectivity of science; organization of science in universities